DETECTION AND SYSTEMATIZATION OF SIGNS AND MARKERS OF MODIFICATIONS IN MEDIA CONTENT FOR THE DEVELOPMENT OF A METHODOLOGY TO ENHANCING CRITICAL THINKING IN THE ERA OF DEEPFAKES - Chemerys, Hanna (Physical and Mathematical Education, 2024)
Modernity demonstrates a critical need for pedagogical support and the development of a methodology to enhance critical thinking in the face of escalating misinformation and advanced media manipulation, mainly through deepfake technology. The paper focuses on creating a comprehensive framework for detecting manipulated content and identifying indicators such as pixelization, unnatural expressions, etc. With attention to international and Ukrainian efforts, the work advocates for ongoing research adapted to evolving technologies to improve media literacy programs in combating emerging forms of misinformation.Problem statement. The problem is the urgent need for a comprehensive methodology that fosters critical thinking skills to combat disinformation and manipulation of artificially reproduced media content, particularly in the context of emerging technologies like deepfakes. The challenge involves assessing existing pedagogical approaches, addressing gaps, and equipping both learners and educators to navigate the complexities of the digital age. Digital transformation, in general, and the spread of artificial intelligence for media generation, in particular, are irreversible processes in the modern world, so the urgent issue, given the challenges of the digital economy and the needs of the digital society, is to find forms, methods, and means of shaping the critical thinking of citizens to counteract manipulation and disinformation by synthetically reproduced media content. It is essential to develop a database with systematically organized materials categorized based on identified markers for the subsequent creation of training materials to solve the outlined issues.Materials and methods. A comprehensive approach was employed, combining general (systemic, instrumental, and functional approaches, dialectical and comparative analysis, synthesis, and systematization for the study of pedagogical, scientific-technical, and methodological literature), specific (observation and analysis of educational practices), and general-logical methods (extrapolation, induction, and deduction for formulating conclusions) in scientific research to solve the tasks set in the study. This allowed for the examination of the current state, evaluation of the practical results of implementing the developed methodology for critical thinking formation, and identification of priority avenues for improving education in the context of the strategy to enhance media literacy and critical thinking among the population and science. The study aimed to determine priority pathways within the framework of the development of methodology of critical thinking and pedagogical support to counteract disinformation and manipulation of artificially reproduced media content and to characterize its potential scientifically. The development of critical thinking and pedagogical support to counteract disinformation and manipulation of artificially reproduced media content requires the following materials analysis: scientific-technical literature (materials offering a scientific understanding of the technical aspects related to media content creation, modification, and reproduction), methodological literature (guides and methodologies focused on developing educational frameworks and strategies to enhance critical thinking in the context of media literacy), synthetically reproduced media content (media content, especially in the context of emerging technologies like deep fake to identify modification markers).Results. The study is devoted to analyzing, identifying, and systematizing markers and signals for identifying media manipulation to create a database for the methodology in the form of methodological cards. A comprehensive database with classification is being developed, focusing on methodological interactive cards with 66 curated cases of deepfakes and synthetically reproduced media (in Ukrainian). This initiative aims to provide educators, researchers, and learners with a versatile resource for understanding the challenges posed by manipulated media.Conclusions. In response to the escalating threat of disinformation and advanced media manipulation, there is a critical need to develop a robust methodology for enhancing critical thinking skills. The study highlights global concerns about false information, mainly through deepfake technology, jeopardizing public trust and enabling psychological manipulation. Future research should consider revising media literacy programs to elevate citizens' critical thinking in the face of evolving digital landscapes and the increasing capabilities of artificial intelligence in generating media content.
Keywords: Deepfake Technology; Artificial Intelligence; Generative Images; Misinformation; Media Literacy; Critical Thinking; Digitalization; Information Warfare; Public Awareness; Synthetic Media Conten